2010
DOI: 10.1371/journal.ppat.1001100
|View full text |Cite
|
Sign up to set email alerts
|

High Content Phenotypic Cell-Based Visual Screen Identifies Mycobacterium tuberculosis Acyltrehalose-Containing Glycolipids Involved in Phagosome Remodeling

Abstract: The ability of the tubercle bacillus to arrest phagosome maturation is considered one major mechanism that allows its survival within host macrophages. To identify mycobacterial genes involved in this process, we developed a high throughput phenotypic cell-based assay enabling individual sub-cellular analysis of over 11,000 Mycobacterium tuberculosis mutants. This very stringent assay makes use of fluorescent staining for intracellular acidic compartments, and automated confocal microscopy to quantitatively de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
153
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(159 citation statements)
references
References 56 publications
6
153
0
Order By: Relevance
“…S2) are shown to be regulated by PhoP (5), and some of these proteins critically contribute to regulation of M. tuberculosis virulence (45,46). In agreement with these studies, more recently acyltrehaloses have been shown to influence phagosome maturation in macrophages (47). FIGURE 7.…”
Section: Discussionsupporting
confidence: 64%
“…S2) are shown to be regulated by PhoP (5), and some of these proteins critically contribute to regulation of M. tuberculosis virulence (45,46). In agreement with these studies, more recently acyltrehaloses have been shown to influence phagosome maturation in macrophages (47). FIGURE 7.…”
Section: Discussionsupporting
confidence: 64%
“…Interestingly, in a screen for M. tuberculosis mutants with decreased ability to arrest phagosome maturation in human macrophages, a mutant was found in the homologue of wecE. M. tuberculosis does not produce LOS, and disruption of this gene was shown to be responsible for the increased biosynthesis of a sulfoglycolipid, which, in purified form, actually promotes phagosome acidification and therefore presumably mycobacterial killing (51). Further research is required to study the mechanism of the observed hypervirulence associated with LOS-IV deficiency, which could tell us more about the interaction of mycobacteria with its host.…”
Section: Discussionmentioning
confidence: 99%
“…Mycobacterial proteins and enzymes, such as the lipid phosphatase SapM and the tyrosine phosphatase PtpA, the lipoamide dehydrogenase LpdC, the metalloprotease Zmp1, the serine/threonine kinase PknG, and the PE-PGRS62 protein, among others, were also involved in this process (Walburger et al 2004;Vergne et al 2005;Deghmane et al 2007;Bach et al 2008;Thi et al 2013). Additional microbial components identified through various genetic screening approaches are also involved in impaired intracellular trafficking of mycobacteria (Pethe et al 2004;Stewart et al 2005;Brodin et al 2010). Distinguishing which of these factors directly contribute to phagosome maturation arrest from those required for bacterial fitness, and whose genetic alteration might result in an aberrant microbial trafficking inside host cells, is difficult.…”
Section: Phagosome Maturation Arrestmentioning
confidence: 99%